2019
DOI: 10.2147/ndt.s227196
|View full text |Cite
|
Sign up to set email alerts
|

<p>Clozapine As Transformative Treatment In Bipolar Patients</p>

Abstract: Clozapine is an atypical antipsychotic used in treatment-resistant bipolar disorder. There is evidence for its anti-suicidal, anti-aggressive properties and efficacy in substance use comorbidities. Despite guidelines, the drug is used in 1.5% of bipolar patients only. Considering its effectiveness in treatment-resistant cases as well as its epigenetic effects it may become transformative treatment in bipolar disorder impacting the clinical course and psychosocial burden of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 50 publications
0
14
0
1
Order By: Relevance
“…However, in a recent review of literature, clozapine was shown as an effective and safe treatment in resistant BD, with lower severe adverse effects reported than those reported in the published schizophrenia literature, with just 0.3% of agranulocytosis (61). Therefore, and considering its unique properties (including its antisuicidal effects and by extrapolation from its likely superiority in treating psychosis (62)), it is becoming more used and seen by many as a useful treatment in resistant BD (63, 64).…”
Section: Resultsmentioning
confidence: 99%
“…However, in a recent review of literature, clozapine was shown as an effective and safe treatment in resistant BD, with lower severe adverse effects reported than those reported in the published schizophrenia literature, with just 0.3% of agranulocytosis (61). Therefore, and considering its unique properties (including its antisuicidal effects and by extrapolation from its likely superiority in treating psychosis (62)), it is becoming more used and seen by many as a useful treatment in resistant BD (63, 64).…”
Section: Resultsmentioning
confidence: 99%
“…Early-onset schizophrenia occurs before age 18; very early-onset schizophrenia (EOS) or childhood-onset schizophrenia (COS) begins at under 13 years old and is extremely rare [ 118 ]. It is well known that EOS has a poorer prognosis and more severe symptoms, as it affects the individual before the brain and personality are fully developed.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, CLZ has been utilized as an antipsychotic drug due to its simultaneous affinity for both dopamine and serotonin receptors [ 28 ]. Nonetheless, its complex mechanisms of action are not yet fully known, involving the modulation of norepinephrine, the regulation of the endocrine system (including pregnenolone and cortisol), the intracellular system-dependent modulation of N -methyl- d -aspartate (NMDA) receptor expression, brain-derived neurotrophic factor up-regulation, and the regulation of the arachidonic acid cascade [ 29 , 30 , 31 , 32 ]. Herein, we performed an integration of the genomic and epigenomic data of CLZ-associated phenotypes to identify genes related to the potential mechanisms of action of CLZ and possible pharmacogenomic applications.…”
Section: Discussionmentioning
confidence: 99%